Economic-mathematical model of optimization of expenses investment-building project payment automobile - Zagursky, O. М.; Kukanov, V. V. (НУБіП України, 2018)
The multivariance of the methods of developing investment and construction projects leads to the need to analyze existing and construct new economic and mathematical models that take into account the likelihood of the implementation of certain options, and also take into account the conditions of uncertainty and risk. In the field of motor transport infrastructure, investment and construction projects are always large-scale and costly, because their implementation affects different components of socio-economic development of territories. Investment-building projects of toll roads, in general, are difficulty managed systems that change their configuration in the course of multi-step processes. The ability to manage such a system causes the problem of choosing one or another action and inevitably leads to the task of finding the optimal solution in terms of management. In the article an algorithm of the economic-mathematical model of optimization of expenses of investment-construction project of a paid motorway in the conditions of uncertainty and risk is developed. The description of the system’s work is based on the "Markovian" decision-making processes, and optimization of expenses was carried out by methods of discrete and dynamic programming, in accordance with the general concept of analysis and optimization of multi-step tasks. The proposed model can be a tool in the operational management of the process of developing an investment and construction project, on the basis of which will be further developed the schedules and calendar plan for its implementation.
Модель оптимізації витрат інвестиційно-будівельного проекту платної автомобільної дороги
Багатоваріантність методів розробки інвестиційно-будівельних проектів призводить до необхідності аналізу існуючих і побудови нових економіко-математичних моделей, що враховують ймовірності здійснення тих чи інших варіантів, а також враховують умови невизначеності і ризику. У сфері автотранспортної інфраструктури інвестиційно-будівельні проекти завжди масштабні та затратні, тому, що їх реалізація впливає на різні складові соціально-економічного розвитку територій. Інвестиційно-будівельні проекти платних автомобільних доріг, взагалі являються складно керованими системами, що змінюють свою конфігурацію в ході багатокрокових процесів. Можливість здійснювати управління такою системою зумовлює виникнення проблеми вибору тих чи інших дій і неминуче призводить до задачі пошуку оптимально доцільного рішення з точки зору управління. В статті розроблено алгоритм економіко-математичної моделі оптимізації витрат інвестиційно-будівельного проекту платної автомобільної дороги в умовах невизначеності та ризику. Опис робіт системи виконано на основі «марковських» процесів прийняття рішень, а оптимізація витрат здійснена методами дискретного та динамічного програмування, відповідно до загальної концепції аналізу і оптимізації багатокрокових завдань. Запропонована модель може бути інструментом в оперативному управлінні процесом розробки інвестиційно-будівельного проекту, на основі якого в подальшому будуть побудовані графіки і календарний план його реалізації.
Keywords: costs; dynamic programming; investment-construction project; economic-mathematical model; paid motorway; risk; витрати; динамічне програмування; інвестиційно-будівельний проект; економіко-математична модель; платна автомобільна дорога; ризик